Has Noninvasive Prenatal Testing Impacted Termination of Pregnancy and Live Birth Rates of Infants With Down Syndrome?. Issue 5 (May 2018) - Hill, Melissa; Barrett, Angela; Choolani, Mahesh; Lewis, Celine; Fisher, Jane; Chitty, Lyn S.
Abstract : (Abstracted from Prenat Diagn 2017;37:1281–1290) Noninvasive prenatal testing (NIPT) for aneuploidy using cell-free DNA (cfDNA) has become widely available and popular for detection of Down syndrome (DS) because of its high sensitivity (99%) and specificity (99.5%). The acceptance of NIPT as an alternative to the first-trimester combined test has greatly reduced the use of invasive prenatal diagnostic testing.